The effect of brand assets on firm value and credit ratings – Evidence from Korea - Mi-Young Shin; Kyunbeom Jeong (Cogent Business & Management, 2024)
This study aims to empirically analyze the impact of brand assets, a company's core competency, on firm value and credit ratings using companies listed on the KOSPI and KOSDAQ from 2011 to 2019. We also investigate the moderating effect of a firm's life cycle on the impact of brand assets on firm value and credit ratings by dividing the life cycle into growth, maturity, and decline stages, according to the economic characteristics and development process of the company. The results show that brand assets have a positive impact on firm value and credit ratings and that the impact of brand assets on firm value and credit ratings is greater for firms in the growth stage than for firms in other stages. Our findings on the effects of brand assets on firm value in the capital market and credit ratings in the bond market suggest that there is a need for broader recognition of brand assets as a source of future earnings and value creation, and a redefinition of financial reporting standards.
Keywords: 650; Brand assets; firm value; credit ratings; firm life cycle